GAMBARAN PENGETAHUAN KELUARGA PASIEN TENTANG PENYAKIT TBC PARU DI CLINIC SÃO JOAQUIM MAUBISSE POSTO ADMINISTRATIVO MAUBISSE - Santos, Domingas Soares dos; Marni, Marni; Herculano, Hermenengildo; Soares, Domingos (Jurnal AKPER GSH, 2021)
Introduction: Knowledge of pulmonary tuberculosis is needed by the public because pulmonary tuberculosis is a contagious disease. The tendency in community life in which there are family members suffering from tuberculosis will have a risk of transmission for family members who live in one house. Purpose: This study is to describe the knowledge of the family about pulmonary tuberculosis in Clinica São Joaquim Maubisse Posto Administrativo Maubisse. Methods: The design in this study was descriptive. The population is all heads of families whose family members suffer from pulmonary tuberculosis in the Clinica São Joaquim Maubisse Posto Administrativo Maubisse, with a sample of 39 respondents using probability sampling techniques using the Simple Random Sampling type. This research variable is family knowledge about pulmonary tuberculosis. Data collection used questionnaires, while data processing by editing, coding, scoring, tabulating, data analysis using frequency distribution tables and narration. Results: it was found that some families of TB patients who had sufficient knowledge about TB disease were (67%) respondents and those who obtained good knowledge were (33%) and with less knowledge there were no respondents (0%). Conclusion: most respondents have sufficient knowledge about pulmonary tuberculosis. So the respondent is expected to increase their knowledge about Tuberculosis and how it is transmitted both from printed and electronic media counseling which is useful to prevent the increase of Tuberculosis sufferers